2014
DOI: 10.1186/1866-1955-6-36
|View full text |Cite
|
Sign up to set email alerts
|

PreImplantation factor (PIF*) promotes embryotrophic and neuroprotective decidual genes: effect negated by epidermal growth factor

Abstract: BackgroundIntimate embryo-maternal interaction is paramount for pregnancy success post-implantation. The embryo follows a specific developmental timeline starting with neural system, dependent on endogenous and decidual factors. Beyond altered genetics/epigenetics, post-natal diseases may initiate at prenatal/neonatal, post-natal period, or through a continuum. Preimplantation factor (PIF) secreted by viable embryos promotes implantation and trophoblast invasion. Synthetic PIF reverses neuroinflammation in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…PIF promotes endometrial receptivity independent of progesterone and trophoblast invasion [15, 2023]. To establish embryo/maternal dialogue, PIF binds systemic CD14+ cells (monocytes) and mitogen-activated lymphocytes, reducing proliferation and leading to TH2/TH1 cytokine bias.…”
Section: Introductionmentioning
confidence: 99%
“…PIF promotes endometrial receptivity independent of progesterone and trophoblast invasion [15, 2023]. To establish embryo/maternal dialogue, PIF binds systemic CD14+ cells (monocytes) and mitogen-activated lymphocytes, reducing proliferation and leading to TH2/TH1 cytokine bias.…”
Section: Introductionmentioning
confidence: 99%
“…The notochord is the first and most vulnerable structure in the embryo and PIF may already support its development. This early protection by PIF may also prevent the development of neurodevelopmental disorders in both children and adults (Duzyj et al, 2014). Thus, PIF has an evolving protective role, from the earliest stages of pregnancy, and can prevent pregnancy complications and perhaps even extend its effect to the post-natal period.…”
Section: The Second Critical Element For Pregnancy Success: Effectivementioning
confidence: 99%
“…Clustering analysis indicated that beyond the central role of HLA-G and FOXP3, PIF also reduced the EGF receptor, which interacts with harmful LMNA and PDIA proteins. This is relevant, since PIF’s pro-receptive effect on the decidua was negated by EGF [30]. Hence, the proteome analysis substantiates PIF’s multifaceted role in regulating the activity of the trophoblast, acknowledging that it is a transformed cell line.…”
Section: Discussionmentioning
confidence: 90%
“…IL-10 enhances HLA-G transcription in first trimester human trophoblast cultures [73, 74]. In the endometrium PIF and P4 create a pro-inflammatory milieu by increasing IL-1β, IL-8, GM-CSF and IFN-γ secretion to promote embryo implantation [29, 30, 36]. Elevated TGF-β could promote IL-1-induced T-cell proliferation and trophoblast invasion by up-regulating integrin expression, as shown for PIF in the endometrium, independent of P4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation